DISSECTING STUDENT MISCONSTRUCTION IN TRANSFORMATIONAL ACTIVITIES SOLVES PROBLEMS THAT ALLOW COGNITIVE CONFLICT TO OCCUR - Rosimanidar Rosimanidar; Purwanto Purwanto; Erry Hidayanto; I Made Sulandra (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
The transformative activity was crucial for problem-solving. In resolving problems, cognitive conflicts could arise, characterized by construction errors marked by deviations or differences from scientific concepts. Eight of the 106 students who experienced cognitive conflicts made construction errors in transformative activities. These errors were categorized into four groups. This research aimed to describe students' construction errors in transformative activities when solving problems that might lead to cognitive conflicts. The research design was phenomenological, with four subjects selected and one student from each group. Student responses and interview results served as research data, analyzed through narrative text analysis. The research findings revealed four forms of construction errors in students during transformative activities in problem-solving that might lead to cognitive conflicts: (1) pseudo construction "correct," occurring when students provide a correct answer to a problem, but upon closer examination, it was found that the clarification of the answer was incorrect; (2) pseudo construction "incorrect," happening when students gave an incorrect answer to a problem, but upon closer examination, the students had a correct thought process and could provide the right answer; (3) hole construction errors, occurring when there were inconsistencies in the construction process of concepts in students' minds; and (4) mis-analogical construction errors, occurring when students made errors in analogizing a problem with representations of other concepts. These four construction errors occurred in transformative activities based on incomplete rule-based systems. Examining these construction errors allowed instructors to improve students' transformative thinking activities according to linear equations with one variable.Aktivitas transformasional sangat penting dalam menyelesaikan masalah. Dalam penyelesaian masalah kemungkinan terjadi konflik kognitif, yaitu kesalahan konstruksi yang ditandai ada penyimpangan atau perbedaan dengan konsep ilmiah. Mahasiswa mengalami konflik kognitif sebanyak 106 orang dan 8 mahasiswanya telah melakukan kesalahan konstruksi dalam aktivitas transformasional. Penelitian ini bertujuan untuk mendeskripsikan kesalahan konstruksi mahasiswa dalam aktivitas transformasional menyelesaikan masalah yang memungkinkan terjadi  konflik kognitif. Jenis penelitian ini adalah fenomenologi dengan dipilih 4 subjek penelitian yang masing-masing 1 mahasiswa dari setiap kelompok tersebut. Jawaban mahasiswa dan hasil wawancara digunakan sebagai data penelitian. Data penelitian dianalisis melalui analisis teks naratif. Temuan penelitian diperoleh bahwa ada empat bentuk kesalahan konstruksi mahasiswa yang dibedah dalam aktivitas transformasional menyelesaikan masalah yang memungkinkan terjadi konflik kognitif, yaitu (1) pseudo construction “benar” yang terjadi saat mahasiswa memberikan jawaban benar terhadap suatu permasalahan, namun ketika ditelusuri, ternyata mahasiswa salah dalam memberikan klarifikasi jawaban; (2) Kesalahan pseudo construction “salah” yang terjadi saat mahasiswa memberikan jawaban salah terhadap suatu permasalahan, namun ketika ditelusuri mahasiswa mempunyai cara berpikir yang benar dan dapat memberikan jawaban yang benar; (3)Kesalahan lubang konstruksi (hole construction) yang terjadi saat proses konstruksi konsep dalam pikiran mahasiswa ada yang tidak sesuai;  dan (4) kesalahan mis-analogical construction yang terjadi saat mahasiswa membuat kesalahan dalam menganalogikan masalah dengan representasi konsep lain. Keempat kesalahan konstruksi tersebut terjadi pada aktivitas transformasional berbasis aturan tidak lengkap (incomplete rule-based). Penelaahan kesalahan konstruksi ini dijadikan dasar bagi dosen untuk memperbaiki aktivitas berpikir transformasional mahasiswa sesuai konsep persamaan linier satu variabel